2014
DOI: 10.1111/ijpo.273
|View full text |Cite
|
Sign up to set email alerts
|

Liver enzymes and clustering cardiometabolic risk factors in European adolescents: the HELENA study

Abstract: Higher GGT and lower AST/ALT are associated with higher cardiometabolic risk factors and their clustering in male and female European adolescents, whereas the associations of ALT were gender dependent. Our results suggest the usefulness of AST/ALT as a screening test in the assessment of adolescents with high cardiometabolic risk and provide gender- and age-specific thresholds that might be of clinical interest.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
25
1
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(31 citation statements)
references
References 40 publications
4
25
1
1
Order By: Relevance
“…In youth population however, Labayen et al [ 31 ] showed a positive association between a higher number of ideal CVH metrics behaviors/factors with lower gamma-GT and ALT in 637 European adolescents. Similarly, Labayen et al [ 32 ] observed a lower aspartate aminotransferase/ALT ratio was also associated with higher cardiometabolic risk factors and their clustering in 1,084 male and female European adolescents. Regarding the FLI ( an algorithm for predicting fatty liver ), few previous studies have reported on the relationship between FLI and cardiometabolic risk factors and their clustering in adults.…”
Section: Discussionmentioning
confidence: 87%
“…In youth population however, Labayen et al [ 31 ] showed a positive association between a higher number of ideal CVH metrics behaviors/factors with lower gamma-GT and ALT in 637 European adolescents. Similarly, Labayen et al [ 32 ] observed a lower aspartate aminotransferase/ALT ratio was also associated with higher cardiometabolic risk factors and their clustering in 1,084 male and female European adolescents. Regarding the FLI ( an algorithm for predicting fatty liver ), few previous studies have reported on the relationship between FLI and cardiometabolic risk factors and their clustering in adults.…”
Section: Discussionmentioning
confidence: 87%
“…However, information regarding the distribution of liver enzymes and their association with cardiometabolic risk factors is scarce in relation to children and adolescents. 30 ALT is a specific liver enzyme that relates to the cytosolic component of hepatocytes. 5 On the other hand, other liver enzymes, including aspartate transaminase (AST), are also released from other organs such as the heart, skeletal muscles, kidneys, brain, pancreas and red blood cells.…”
Section: Discussionmentioning
confidence: 99%
“…The AST/ALT ratio thresholds for determining that adolescents presented high cardiometabolic risk were 1.00 for younger males, 0.74 for older males, 0.86 for younger females and 0.87 for older females. 30 Mohammadi et al reported that there was a strong association between high levels of ALT, AST and ALT/AST ratio and most cardiometabolic risk factors. This relationship was independent of anthropometric indexes.…”
Section: Discussionmentioning
confidence: 99%
“…It was found that elevated ALT level was weak surrogate marker for MetS and CMRF clustering. However, excess adiposity can result in hepatic insulin resistance, hepatic steatosis, and Nonalcoholic fatty liver disease (NAFLD), well-known components of MetS [ 28 , 29 ]. Some studies showed that low ALT level is associated with ideal cardiovascular health behavior [ 30 ] and MetS has been shown to have a dose-response relationship with ALT level [ 31 ].…”
Section: Discussionmentioning
confidence: 99%